(3TQM Yjhf GdeSGFds - (3eMeO CHh YHO Gddg Hf Rjf GdOjf YHO GdMejO GdHNGQjs; (3CHh GddjK GdSeQbfOj , GeGe GdgOj,J (B373 (3g` s ((3YeQ Hf ESeGYjd GdMfai s)
(3ChdgG (B:s
(3jHOC HHGH GdWgGQI s
(3BNQgG (B:s
(3hfSJhab Gddg JYGdi Edjg fJhH hfSCdg GdYUeI ef GdRdd hGdNWGjG heG jhLH GdYbGH GfJgi HMeO Gddg hefg s
(3HChdg agQSJs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1187s
Keywords: (3Gdabg GdMfajs